Patterns of Digital Transformation: Stories From Afghanistan’s Public Administration - Mohammad Yusuf Momand; Valentino Vranic (IEEE Access)
In its digital transformation, Afghanistan faces numerous challenges. This paper brings twenty eight patterns of digital transformation related to people and to systems and services that address these challenges. The patterns are organized into a pattern language with connections that indicate typical directions in which these patterns are applied, forming meaningful pattern sequences. We discovered the patterns by observing the actual efforts of digital transformation of public administration in Afghanistan, which we present in the paper as stories: stories about the challenges of digital transformation and patterns that help address these challenges. At the time of our observations, some patterns were already present, which is evident in the stories of digital transformation in Afghanistan we observed in reality and which we included in the paper, but they were not recognized as such and not referred to by the names we set for them in this paper. We assessed the relevance of the patterns we identified in a broader context via a survey we conducted with the participants actively engaged in or influenced by the implementation of digital initiatives in Afghanistan. With the pattern language presented in this paper, practitioners can learn from proven solutions and consolidate their vocabulary so they can build their own solutions in a more synergistic way.